THE LANGUAGE TOOLS OF MOSCOW DESCRIPTION IN I. BUNIN’S “CURSED DAYS” ESSAY. - HOVHANNESYAN, GAYANE (Bulletin of Yerevan University H: Russian Philology, 2020)
This article deals with some features of the language of Ivan Bunin's political essay “Cursed Days”. Much attention is paid to the way the author describes old traditional Moscow in the context of new revolutionary Russia.The research is devoted to the analysis of different grammatical tools that reflects the author's position on the changing system of politics, morality, and religion
Keywords: “Cursed Days”, Moscow, memory, formal grammatical means, rhythm, sound replay, lexical-syntactic replay